Information literacy among secondary school students at fully residential schools in Kuala Lumpur / Nor Hashimah Hussain - Nor Hashimah , Hussain (2007)
The research was undertaken to examine aspects of information literacy among secondary school students at fully residential schools in Kuala Lumpur. The focus of this study was on information literacy skills, problems associated with it, sources of information preferred by the students, programmes conducted at school resource centres and the need for information literacy from students and teachers perspective. The instruments for the study were two sets of questionnaires. The first set was distributed to 300 Form 1, 2 and 4 students from three residential schools in Kuala Lumpur. The study revealed that 81.7 % respondents had the skills to define their need for information, 74.7 % knew how to locate information by accessing the Net and 93.3% had the skills to look at the content when selecting for information. To organize and use information, respondents preferred to use paper based media and they used information by identifying important points and then arranging it for the task at hand. Mind-mapping method was chosed by 53.3% of the students for presentation. Electronic resources were chosen by 63% respondents to locate information and the problems that they faced were time constraint (52.7%) and unavailable resources (66.7%). The main reasons for chosing Internet was easier and faster to retrieve information. To select information, 6.7% stated they did not know how to choose the most accurate information. It was also found that there were very few programmes conducted in school resource centres regarding the use of materials for learning purpose. Finally, the need for information literacy from students perspectives revealed that selecting accurate information (65.3%) were deemed to be the most useful skills to them. The second set of questionnaires was distributed to the 15 teachers to probe the depth of the implementation of programmes in school resource center and the problems associated with conducting it. Findings shows constraints and lack of skills in organizing school resource centres.